Implementasi Pelaksanaan Asessmen Nasional Berbasis Komputer (ANBK) di SDN 01 Benteng Hulu - Lahagu, Siti Nuraini; Panduwinata, Tiara (ALACRITY : Journal of Education, 2024)
This study aims to find out how the implementation of the ANBK exam will affect SDN 01 Benteng Hulu from 2021 to 2023. More than that, this study also explains how the school integrates learning ANBK questions that are literacy and numeracy through learning materials in the classroom environment and conducting simulations before the implementation of the ANBK exam. The method in this study is a quantitative method by observing and collecting school archive data related to the ANBK exam and conducting direct interviews with the school. The implementation of the ANBK exam, which has been running since 2021, 2022, and 2023, shows that the implementation of the ANBK exam at SDN 01 Benteng Hulu runs smoothly, which can be seen in the readiness of students when carrying out the ANBK exam. In its application, the ANBK exam uses a computer and laptop for each student and carries out the exam by dividing the time into two shifts, namely the morning and afternoon shifts filled by 15 students per exam.